Study Of Regional Development Bank Performance And Regional Economic Growth - Marsetyo Adi Nugroho; Rr. Iramani (Yayasan Riset dan Pengembangan Intelektual, 2023)
Economic growth is a serious concern for a region because it is a measuring tool to determine its economic condition and what policies must be taken. Many factors influence the increase in economic growth. In this study, the effect of regional development bank (BPD) performance was examined, namely related to lending, collection of third-party funds (DPK), and profitability on economic growth. The research method used was panel data regression. The results of this study show that only the variables of credit distribution have a positive and significant effect on economic growth. The results of this study are expected to be useful inputs for both local governments and BPD in increasing economic growth. This research implies that there is a need for positive collaboration and synergy between local governments and BPD, especially in terms of lending to the community which is expected to stimulate purchasing power, encourage trade and investment so that it can provide a multiplier effect on economic growth.